2018
DOI: 10.1007/s11892-018-1027-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Prevent Readmission in High-Risk Patients with Diabetes: the Importance of an Interdisciplinary Approach

Abstract: A review of the current literature revealed several strategies that have been associated with a decreased risk of readmission in high-risk patients with diabetes. These strategies include inpatient diabetes survival skills education and medication reconciliation prior to discharge to send the patient home with the "right" medications. Other key strategies include scheduling a follow-up phone call soon after discharge and an office visit to adjust the diabetes regimen. The authors identified the most successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…The second greatest reduction was observed for diabetic and other retinopathies (H35), which often occurred with type 2 diabetes as the main diagnosis. These findings are in line with reports that a lack of postdischarge outpatient visits in patients with diabetes is one of the strongest risk factors for short-term (30-day) readmissions [ 37 ] and that postdischarge office visits to adjust the diabetes regimen contribute to a decreased risk of short-term readmission [ 38 ]. While there is mixed evidence to which extent poor glycemic control is also a risk factor for longer-term readmission risk [ 13 ], our findings clearly show that specialist care after discharge is related to a strongly significant reduction in readmission risks of down to 62% (men) and 60% (women) compared to patients without such contacts.…”
Section: Discussionsupporting
confidence: 90%
“…The second greatest reduction was observed for diabetic and other retinopathies (H35), which often occurred with type 2 diabetes as the main diagnosis. These findings are in line with reports that a lack of postdischarge outpatient visits in patients with diabetes is one of the strongest risk factors for short-term (30-day) readmissions [ 37 ] and that postdischarge office visits to adjust the diabetes regimen contribute to a decreased risk of short-term readmission [ 38 ]. While there is mixed evidence to which extent poor glycemic control is also a risk factor for longer-term readmission risk [ 13 ], our findings clearly show that specialist care after discharge is related to a strongly significant reduction in readmission risks of down to 62% (men) and 60% (women) compared to patients without such contacts.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with other studies on trends in LOS and 30DR in hospitalized patients with diabetes. A number of studies have found that patients with diabetes have overall higher LOS and/or 30DR [24][25][26][27][28][29][30][31][32] when compared to patients who do not have diabetes. Comino, et al reported that readmission rates in 23,779 study patients with diabetes were between 2-6 times higher than those who did not have diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…The prevention and treatment of neurologic consequences from diabetes should involve a multidisciplinary team. 13,14 These patients should undergo annual or semiannual ophthalmologic evaluations for diabetic retinopathy. Joint guidelines established by the American Academy of Ophthalmology, the American Diabetes Association, and the American College of Physicians recommend annual screening for all postpubertal type I diabetics, and all patients with type II diabetes with disease duration of more than 5 years.…”
Section: Physical Examinationmentioning
confidence: 99%
“…The underlying management of diabetes-related hyperglycemia and diabetic foot ulcers typically requires an interdisciplinary team of experts to optimize medical outcomes. 13,14 Primary care providers may feel comfortable diagnosing and managing uncomplicated presentations of diabetic neuropathy. However, in patients with multiple medical comorbidities and atypical presentations of diabetic peripheral neuropathy, recognition of this diagnosis may be difficult.…”
mentioning
confidence: 99%